AN EMPIRICAL STUDY OF DISCLOSURE PRACTICES OF ACCOUNTING STANDARDS IN INDIA - H.S Bajpayee and Anubha Srivastava (Abhigyan, 2010)
Accounting is nothing but a language to communicate the financial massage to related parties. Since accounting process involves preparation of financial statement therefore every organization is required to prepare financial statement and while preparing theses statement they must follow various accounting policies .There are some policies which can be used discretionally , and it leads to shows different results . Therefore accounting standards issued by ICAI in India prescribes the rules regarding treatment of different items e.g. treatment of fixed asset, depreciation, inventory etc in financial statement. This paper is an attempt to analyze the compliance of accounting standards practices in India by various companies .So far as mandatory accounting standards are concerned all the companies are complying with those all but in case of optional accounting standards there are some , which are disclosing full information regarding their compliance with the accounting standards ,and on the other hand there are some companies which are clarifying the true picture . This makes comparison difficult and as well as it doesn't give true and fair information to various related parties such as investors, employees, customers nd Government. As a conclusion it could be said that that there must be uniformity in financial statement of companies in order to make inter -firm and intra- firm comparison easy.